Analisis Berbagai Jenis Tanaman yang dapat Dimanfaatkan Sebagai Obat, Kosmetik, Rempah, dan Bumbu: Analisis Berbagai Jenis Tanaman - Aritonang, Putri; Akbar, Habil; Sinaga, Maya Febrina; Sinaga, Nadia Rouli; Sastra, Siti Fathiya Dwinda; Sinaga, Yefta Darniati; Nasution, Aswarina; Hasairin, Ashar (Jurnal Sains Indonesia, 2025)
This study aims to examine the use of medicinal plants by the community based on local knowledge that has been passed down from generation to generation. An ethnobotanical approach is used to explore information about the types of medicinal plants, the parts of the plants that are used, how to process them, and the types of diseases that can be treated. Data were collected through literature studies of books, scientific journals, research reports, and other related documents. The results of the study indicate that the community is still very dependent on medicinal plants in their daily medical practices. Various types of plants were found to be used to treat mild to chronic diseases, with processing methods such as boiling, pounding, or brewing. These findings emphasize the importance of preserving local knowledge and conserving medicinal plants as part of a cultural heritage that has great potential in the development of alternative medicine.